2016
DOI: 10.1177/0884533616639126
|View full text |Cite
|
Sign up to set email alerts
|

Increased Force Required With Proposed Standardized Enteral Feed Connector in Blenderized Tube Feeding

Abstract: ENFit adapter implementation is the largest change to home enteral nutrition in more than a decade. Additional rigorous testing is required to ensure that the needs of all patients receiving home enteral nutrition are met prior to widespread adoption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…If BTFs can go through the Cath‐tip syringe, they should also be able to go through the ENFit connector 82 . Another study by Mundi et al 83 observed a need for increased force with the ENFit connector to administer blenderized formulas compared to traditional connectors, but this study was conducted with device prototypes and not with FDA‐approved products. Currently, the FDA and other independent labs are conducting flow and pressure studies with a variety of tubes and a variety of formulas, including blenderized diets.…”
Section: Section 5 Procure Select/prepare Label and Dispense Enmentioning
confidence: 99%
“…If BTFs can go through the Cath‐tip syringe, they should also be able to go through the ENFit connector 82 . Another study by Mundi et al 83 observed a need for increased force with the ENFit connector to administer blenderized formulas compared to traditional connectors, but this study was conducted with device prototypes and not with FDA‐approved products. Currently, the FDA and other independent labs are conducting flow and pressure studies with a variety of tubes and a variety of formulas, including blenderized diets.…”
Section: Section 5 Procure Select/prepare Label and Dispense Enmentioning
confidence: 99%
“…Sullivan et al 8 concluded that these methods of feeding were poorly tolerated compared with continuous feeding through a small bore feeding tube. Recent research conducted by Mundi et al 19 has found that home-made blenderised recipes require more force to push through when using the new ENFit adapter which could have implications for using a blended diet in malnourished patients.…”
Section: Resultsmentioning
confidence: 99%
“…Homemade diets usually have higher viscosity than industrialized ones. Therefore, adequate fluidity is required to avoid the clogging of the catheter or the need to exert excessive pressure on the syringe plunger when the infusion is in bolus, with risk of catheter displacement 21 .…”
Section: Resultsmentioning
confidence: 99%